Explaining Development and Change in Organizations - Ven, Andrew H. Van de; Poole, Marshall Scott (Academy of Management Review, 1995)
This article introduces four basic theories that may serve as building blocks for explaining processes of change in organizations: life cycle, teleology, dialectics, and evolution. These four theories represent different sequences of change events that are driven by different conceptual motors and operate at different organizational levels. This article identifies the circumstances when each theory applies and proposes how interplay among the theories produces a wide variety of more complex theories of change and development in organizational life.